The relationship between team climate and interprofessional collaboration: preliminary results of a mixed methods study - Bailey, Christopher; Agreli, Heloise F.; Peduzzi, Marina (Taylor & Francis, 2016)
Relational and organisational factors are key elements of interprofessional collaboration (IPC) and team climate. Few studies have explored the relationship between IPC and team climate. This article presents a study that 10 aimed to explore IPC in primary healthcare teams and understand how the assessment of team climate may provide insights into IPC. A mixed methods study design was adopted. In Stage 1 of the study, team climate was assessed using the Team Climate Inventory with 159 professionals in 18 interprofessional teams based in São Paulo, Brazil. In Stage 2, data were collected through in-depth interviews with a sample of team members who participated in the first stage of the study. Results from Stage 1 provided an overview of factors relevant to 15 teamwork, which in turn informed our exploration of the relationship between team climate and IPC. Preliminary findings from Stage 2 indicated that teams with a more positive team climate (in particular, greater participative safety) also reported more effective communication and mutual support. In conclusion, team climate provided insights into IPC, especially regarding aspects of communication and interaction in teams. Further research will provide a better understanding of differences and areas of overlap between team climate 20 and IPC. It will potentially contribute for an innovative theoretical approach to explore interprofessional work in primary care settings.